Study of Proportion of Milk with Lesser Yam Filtrate and Starter Concentration for Producing Synbiotic Yoghurt : (Study of Proportion of Milk with Lesser Yam Filtrate and Starter Concentration) - Rosida Rosida; Sintha Soraya Santi; Rohman (Engineering Faculty, University of Pembangunan Nasional Jawa Timur, 2021)
This study aimed to determine the effect of the proportion of cow's milk with lesser yam filtrate and starter concentration on the characteristics of synbiotic yoghurt. The research used a factorial completely randomized design (CRD) with two factors, factor I was the proportion of cow's milk with lesser yam filtrate (100:0; 60:40; 50:50; 40:60; 0:100) and factor II was the starter cocentration (3%, 5%, 7%). The data obtained were analyzed using analysis of variant (ANOVA) and if there was a significant difference between treatments, then continued with Duncan's test at the 5% level. Synbiotic yoghurt from proportion of cow's milk with lesser yam filtrate (50:50) and 5% starter concentration was the best treatment with total Lactic Acid Bacteria of 7.23 log CFU/ml; pH 4.20; total dietary fiber 3.05%, soluble fiber content 1.3%, inulin content 1.2%, fat content 0.41% and soluble protein content 2.66% with an average texture preference score of 6.13 (like much); taste core 6.02 (like much) and smell score 5.20 (like).